Weather - Thomson, Ruth 1949- (Philadelphia Chelsea Clubhouse, 2005)
This series teaches young readers to examine and appreciate paintings and sculptures. It also seeks to help students develop their own creative skills.
First published in the UK by Chrysalis Children's Books in 2005.
"Famous works of art, projects, art tips, picture hunts"--Cover.
Keywords: Weather in art -- Juvenile literature; Art -- Juvenile literature